The International Law Fragmentation: Legal Consequences and Solutions - Emmy Latifah (Sekolah Tinggi Hukum Bandung, 2023)
The development of International Law that is taking place today has led to fragmentation. As a result, conflicts of norms arise from international treaties generated by each regime. This study aims to examine how conflict of norms can take place in a fragmented international law system and how to resolve it. It is normative legal research, used secondary data in the form of primary legal materials, secondary legal, and tertiary. The data collection technique uses library reserach, then analyze qualitatively. The results indicate that the absence of an authorized institution to create International Law causes conflict of norms International Law. The ways to resolve conflict of norms include not applying one of the conflicting norms; considering one of the conflicting norms is illegal; taking into consideration one of the conflicting norms is still valid but not illegal; and the two conflicting norms are considered to have the same position.